Oxidation of Ethanolamine by Potassium Permanganate in the Presence and Absence of Sodium Dodecyl Sulphate: A Kinetic Study in an Acidic Medium - Latona, Dayo (Makara Journal of Science, 2023)
The kinetics of ethanolamine oxidation by acidified KMnO4 was investigated in the absence and presence of sodium dodecyl sulfate (SDS) was investigated using a pseudo-first-order kinetics approach, with [ethanolamine]o >> [KMnO4]o. The measurements were conducted at λmax = 525 nm using an ultraviolet/visible-1800 Shimadzu spectrophotometer. The stoichiometry showed that 2 moles of KMnO4 were consumed by 5 moles of ethanolamine in the aqueous medium. The reaction orders in both the aqueous and micellar media remained the same with a first-order dependence on [KMnO4] and [ethanolamine] and a fractional-order dependence on [H+]. The dependence on [H+] was in the form of kobs = a + b[H+], and the Michaelis-Menten plot showed the existence of an intermediate complex. The Fourier-transform infrared spectrum suggested the conversion of the OH group in ethanolamine to aldehyde. Activation parameters were obtained from the Arrhenius and Eyring equations as follows: ∆H# = 22.12 kJ mol-1, ∆S# = -0.224 kJ K-1 mol-1, and ∆G# = 88.87 kJ mol-1 in the aqueous medium, and ∆H# = 26.38 kJ mol-1, ∆S# = -0.191 kJ K-1 mol−1, and ∆G# = 83.298 kJ mol-1 in the micellar medium. The similarity in ∆G# values in both media suggests the occurrence of the same reaction mechanism, and the negative ∆S# suggests a rigid transition state and association mechanism. The polymerization test revealed the absence of free radicals, indicating that one-electron oxidation leading to the formation of free radicals could be ruled out. Additionally, Menger–Portnoy’s and Piszkiewicz’s cooperativity models were employed to analyze the micellar effect.